Depressive symptoms among Thai male seafarers during the COVID-19 pandemic: a cross-sectional study - Woraluk Jonglertmontree; Orawan Kaewboonchoo; Ikuharu Morioka; Plernpit Boonyamalik (BMC, 2023)
Abstract Background Prevalence of depressive symptoms among seafarers is higher than the general population because of their unique work conditions. Factors that can be changed must be considered and promptly addressed in order to decrease the prevalence of depression. This study aims to clarify the prevalence of depressive symptoms and its related factors among Thai seafarers in an effort to contribute to policies and to prevent depression among Thai seafarers. Methods This cross-sectional study was conducted among 381 male seafarers working onboard ocean-going vessels of five Thai shipping companies. The questionnaire items comprised of personal factors, working factors and depressive symptoms. Depressive symptoms were assessed using the Thai version of the Patient Health Questionnaire-9. First, the chi-square test was used for univariate analysis. Then, variables significantly associated by the chi-square test were used for multivariate logistic regression analysis (employing the stepwise method) as independent variables. Results The average age of participants in this study was 36.4 years. Prevalence of depressive symptoms was 19.5%. One half of the participants (58.3%) reported subjective sleep problems, and most (75.1%) experienced poor coping behaviors. Two thirds (67.5%) were officers, and 10.1% of participants reported that they sometimes or never performed occupational safety behaviors. Regarding work environments, 62.2% reported that their work was disturbed from performing repetitive tasks. Multivariate logistic regression analysis showed two personal factors; sleep problems (Adjusted Odds Ratio (AOR) = 7.97, 95% Confidence interval (CI) = 3.52-18.05) and poor coping behaviors (AOR = 4.46, 95%CI = 1.61-12.34), and three working factors; job assignment (AOR = 2.50, 95%CI = 1.33-4.70), inadequate occupational safety behaviors (AOR = 4.51, 95%CI = 1.85-11.01) and performing repetitive task (AOR = 2.27, 95%CI = 1.16-4.45), were significantly associated with depression. Conclusion During COVID-19 pandemic, 19.5% of Thai male seafarers had depressive symptoms. Personal and working factors including subjective sleep problems, poor coping behaviors, job assignment, performing inadequate occupational safety behaviors and performing repetitive tasks were risk factors of depressive symptoms among Thai male seafarers. Monitoring work environment rigorously and coping with work-related stress of the occupational safety behaviors program should be suggested.